(380) How to Plan- In The National Panning Everything Has a Price, And Economic Policy Making Means a Compromise Among Several Desideration- Being Memo 102 In The New Series of Professor Frisch كيفية التخطيط - في التخطيط الوطني، لكل شيء كثمن، وصنع السياسات الاقتصادية يعني التوصل إلى حل وسط بين عدة اعتبارات - المذكرة رقم 102 في السلسلة الجديدة للأستاذ فريش - Frisch, Ragnar (The Institute of National Planning, 2025)
The purpose of this model is to use Egyptian data to illustrate how the basic principle described in the title of this memorandum will function in the Egyptian context. I will relax the two simplifying and somewhat unsatisfactory assumptions underlying Model 1. This model is designed to shed light on issues related to the elaboration of the five-year plan set to begin execution in the year 1965/66, starting from July 1, 1965. To maintain generality, I will consider the case where the plan may encompass any number of years. The symbol T will be used to denote the number of years in the plan. هدف هذا النموذج هو استخدام البيانات المصرية لتوضيح كيفية عمل المبدأ الأساسي الموصوف في عنوان هذا المذكرة في السياق المصري. سأقوم بتخفيف الافتراضين المبسطين وغير المرضيين اللذين كانا أساس النموذج الأول. هذا النموذج مصمم لتسليط الضوء على المشكلات المتعلقة بإعداد خطة السنوات الخمس التي ستبدأ تنفيذها في السنة 1965/66، أي في السنة التي تبدأ في 1 يوليو 1965. للحفاظ على العمومية، سأعتبر الحالة التي قد تشمل فيها الخطة أي عدد من السنوات. سيتم استخدام الرمز T للدلالة على عدد السنوات في الخطة.